Legal and constitutional status of race-based and religious-based political parties in Malaysia and Nigeria - Mokhtar, Khairil Azmin; Oba, Abdulmumini A (2011)
Malaysia and Nigeria are multi-religious, multi-ethnic, Muslim-majority democratic countries. The Malaysian system is based on the parliamentary system while Nigeria operates the presidential system. Both countries are federations where elected official run the federal and state governments respectively. Both countries are multi-party states where political parties of various ideological persuasions compete for power. The central question is to what extent does the law allows the existence of racial and religious-based political parties in both countries? This paper explores this theme based on analyses of the constitutions, statutes and case law applicable in the two countries. The study found that the legal status of religion in the state and the status of religion in the electoral process in both countries differ. In Malaysia, Islam is the state religion although the country is a modern nation state and not an Islamic state ran along strict Islamic lines. In Malaysia, electoral laws are silent on the role of religion therefore it is possible to form political parties which are aligned with religious ideologies. The attitude in Malaysia is based on the recognition of the important role religion plays in the identity and aspirations of its peoples. In Nigeria, the constitution disallows the state from having a state religion and prohibits political parties from having ethnic or religious affiliations. The study found further that the different approaches in both countries have their advantages and disadvantages, and that they represent competing approaches to national unity and national integration.